2007
DOI: 10.1007/s10995-007-0202-7
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of Maternal and Perinatal Outcomes Associated with Assisted Reproductive Technology in Massachusetts

Abstract: Women who conceive with ART are more likely than women who do not to enter pregnancy with a chronic condition and develop complications during pregnancy and labor and delivery. Additionally, infants born after ART are at increased risk for adverse health outcomes. The mechanisms underlying these associations require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
91
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 31 publications
9
91
0
1
Order By: Relevance
“…stress [4], and health concerns [5][6][7]. To date, very few studies have assessed the impact of essential trace elements on IVF, although sufficient stores are clearly needed for success [8].…”
Section: Introductionmentioning
confidence: 99%
“…stress [4], and health concerns [5][6][7]. To date, very few studies have assessed the impact of essential trace elements on IVF, although sufficient stores are clearly needed for success [8].…”
Section: Introductionmentioning
confidence: 99%
“…Because twin pregnancies are more prevalent after ART and can modify pregnancy prognosis [2,5,6], we show in Table 2 the pregnancy outcomes only in women who delivered singletons. Smoking rate and weight gain during pregnancy were similar among the groups.…”
Section: Obstetric and Neonatal Outcomesmentioning
confidence: 99%
“…Indeed, after exclusion of twin pregnancies, that carry specific over risks [1,2], the role of the underlying cause of infertility, such as a polycystic ovarian syndrome (PCOS) [8] through the hormonal environment induced by hormonal stimulation and menstrual preconditioning [9], and the role of the diverse types of ovarian stimulation and assisted reproductive technology (ART) procedures with mild or high estrogen levels [10], have been questioned. In the meta-analysis of Boosman et al [8], women with PCOS demonstrated a significantly higher risk of developing pregnancyinduced hypertension (PIH); but two more recent reviews [11,12] suggested that heterogeneous aetiological factors associated with PCOS, such as obesity, could be involved in this adverse outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous studies connecting the use of assisted reproductive technologies (ART), the handling of eggs and sperm outside the human body, such as in vitro fertilization (IVF), with adverse pregnancy outcomes. Even after controlling for multiple gestations, increased rates of preeclampsia, gestational diabetes, preterm delivery, and perinatal mortality are noted [1,2]. Additionally, there have been multiple studies linking ART to negative fetal outcomes such as cerebral palsy, congenital abnormalities, low birthweight, and neurological problems [1,3,4].…”
Section: Introductionmentioning
confidence: 99%